121k views
5 votes
Stella solves the following system of equations using the substitution method.

y=−4x−65x−y=10

What is the single-variable equation she solves after substituting?
A. 5x−4x−6=10
B. 5x−(−4x−6)=10
C. 5x+10=−4x−6
D. 5x+10=−(4x−6)

User IMatoria
by
4.6k points

2 Answers

3 votes

Answer: Stella solves the following system of equations using the substitution method.

y=−4x−65x−y=10

What is the single-variable equation she solves after substituting?

Responses

5x−(−4x−6)=10 CORRECT

5 x minus left parenthesis negative 4 x minus 6 right parenthesis equals 10

5x+10=−(4x−6)

5 x plus 10 equals negative left parenthesis 4 x minus 6 right parenthesis

5x−4x−6=10

5 x minus 4 x minus 6 equals 10

5x+10=−4x−6

5 x plus 10 equals negative 4 x minus 6

Explanation:

sorry for the formatting not sure how that happened

User GSee
by
5.4k points
4 votes

9514 1404 393

Answer:

B. 5x−(−4x−6)=10

Explanation:

The first equation gives an expression for y:

y = -4x -6

When that is used in the second equation, the result is ...

5x -y = 10

5x -(-4x -6) = 10 . . . . . . after substituting; matches B

User Mtl
by
5.8k points